andragógico method: fundamental pillar of teaching in higher education (Revista Electrónica REDINE, 2018)
Education is a complex and multi-faceted process that involves the participation of subjects with the common goal of training people according to the objectives of the State; transmitting the values ​​and governing principles for that historical moment. From this perspective, university education serves to constitute the individuals required by the State in order to preserve established values ​​and promote the development of the nation. In this sense, university education must adapt to the challenges of the changing environment and external influence due to globalization. It is there where the techniques, procedures and strategies followed by teachers have to promote the interaction of students in the pursuit of knowledge by their own means and in accordance with the environment; and since the participant is an adult, the strategies must be linked to this age group, with Andragogy being the key element. The interest of the andragogic process is to maximize individual learning but at the same time the learning of others, creating a harmonious work environment between teacher and student
Keywords: andragogy; university education; teaching methods